Pendampingan Pembinaan Qira’ah Al-Qur’an melalui Penerapan Ilmu Tajwid di Madrasah Diniyah Miftahurrahman Dusun Ngepel Ngebel Ponorogo - Siti Lailatul Maratus Sholikah; Wahyu Hanafi Putra (Social Science Academic, 2025)
This study aims to foster the reading of Surah Al-Fatihah in accordance with the rules of tajwid among students of Madin Miftahurrahman in Dusun Ngepel, Sempu Village, Ngebel, Ponorogo. The research employs demonstration and simulation methods combined with the Asset-Based Community Development (ABCD) approach. The study involved 12 elementary-level students who were guided directly in the learning process by KPM university students and supported by teachers of Madin Miftahurrahman through the stages of observation, practice, and documentation. The findings indicate that the application of demonstration and simulation methods with the ABCD approach significantly contributes to the improvement of students’ ability to recite Surah Al-Fatihah correctly according to tajwid. This learning model proved to be more interactive and contextual as it engaged teachers, students, and KPM university students in active participation. In conclusion, the study suggests that demonstration and simulation methods combined with the Asset-Based Community Development (ABCD) approach can serve as an effective learning strategy for developing accurate recitation of Surah Al-Fatihah in line with tajwid principles.